Conclusion algorithm based on the reconnaissance data processing results - Bayramov, Azad Agalar oğlu; Mammadov, Vugar Mammadhuseyn (Національний технічний університет "Харківський політехнічний інститут", 2020)
As it is known, the investigation of enemy forces, time of the outbreak of hostilities, direction and the kind of activities are the tasks of military reconnaissance. For the purpose of investigation of the directions and fields of gathering of the reconnaissance information, revealing an importance of enemy activities the reconnaissance indications are determined. The reconnaissance indications are determined in accordance with tactical activities (assault, counter-offensive, defence, etc.). The formation of a base of the reconnaissance indications is offered for application these indications in the future. In the paper, the method of conclusion in accodance with reconnaissance indicators has been considered. The method of construction of the algorithms conclusion based on the results recipience of reconnaissance data processing has been offered for solution of the reconnaissance tasks.

Як відомо, військова розвідка розглядає в основному такі завдання: з'ясування сил противника, час початку його дій і направлення дії, а також характер дій. З метою з'ясування напрямків і областей отримання розвідувальної інформації, визначаються розвідувальні ознаки, що виявляють значущість тієї чи іншої діяльності противника. Розвідувальні ознаки визначаються відповідно до тактичних діями (наступ, контрнаступ, оборона тощо). Для подальшого використання цих ознак пропонується створення бази розвідувальних ознак. У статті розглянуті питання і методика виведення висновку за результатами обробки розвідувальних даних відповідно до розвідувальними ознаками. Пропонується спосіб складання алгоритмів для виведення висновку за результатами обробки даних і вирішенні розвідувальних завдань.
Алгоритм виведення висновку на основі результатів обробки розвідувальних даних
Keywords: reconnaissance indications; database; block diagram; розвідувальні ознаки; база даних; блок-схема